Gay Fathers: Disrupting Sex Stereotyping and Challenging the Father-Promotion Crusade - Meyer, Erin Marie (Columbia Journal of Gender and Law, 2011)
This Article addresses the problematic perpetuation of sex- stereotyped parenting roles by courts, commentators, and politicians to whom this Article will refer as the “father- promotion crusaders.” These crusaders assert that “children need a father” and proceed to support this claim by defining “father” in various ways, all of which rely upon sex stereotypes. The promotion of sex stereotyping in the realm of parenting stands in con trast to an anti-sex-stereotyping norm that has begun to take hold in the realm of employment since 1989, the year in which the Supreme Court recognized sex stereotyping in the workplace as a form of sex discrimination in Price Waterhouse v. Hopkins. In that case, the Supreme Court acknowledged that “an employer who acts on the basis of a belief that a woman cannot be aggressive, or that she must not be, has acted on the basis of gender. The Court held that a female employee who failed to receive. a promotion to partnership in her accounting firm because she did not conform to female sex stereotypes could bring a sex discrimination claim under Title VII. A plurality of the Court explained that sex stereotyping in the workplace is of legal relevance because: “[W]e are beyond the day when an employer could evaluate employees by assuming or insisting that they matched the stereotype associated with their group, for in forbidding employers to discriminate against individuals because of their sex, Congress intended to strike at the entire spectrum of disparate treatment of men and women resulting from sex stereotypes.”